The sport, vector of regionalization / globalization Case study: International Volleyball Federation (FIVB) - Grigore Vasile HERMAN; Mariana Szabo-Alexi; Paul Szabo-Alexi; Paul Florian Dragoş; Marius Marinău (Editura Universităţii din Oradea, 2018)
The present study aims at highlighting some of the defining aspects of how sport, in this case the volleyball represented by the Federation International Volleyball (FIVB) plays a decisive role in shaping and substantiating the concepts of globalization and regionalization. In this respect, two essential aspects were analyzed, one on the institutional organization of volleyball as a sport and the other on global competitions.